CULTIVAR MIXTURE IMPROVED YIELD AND WATER USE EFFICIENCY VIA OPTIMIZATION OF ROOT PROPERTIES AND BIOMASS DISTRIBUTION IN MAIZE (ZEA MAYS L.) - Wang, Xiaolin; Chen, Yinglong; Zhang, Suiqi (Emirates Journal of Food and Agriculture, 2017)
Use of chemical fertilizer and high-density plantings has increased maize productivity in semi-arid regions. With high-density planting, interaction among individuals may impede or improve sustainable yield and resources use, the elucidation of its effects requires more study. A 2-year field experiment was conducted to evaluate the effects of interaction between two mixed maize cultivars on root properties, biomass distribution and water use. Root biomass and surface area decreased, concomitantly, root hydraulic conductivity was improved because root length density in the 0–30 cm soil layer increased in the mixed crop plots. Lower root to shoot ratios resulted from positive interaction of the two mixed maize cultivars. Consequently, mixed interaction increased the harvest index under high-planting density. Finally, grain yield increased by 2.6%–15.6% and water use efficiency by 4.7%–18.3% with a disproportionate trend in different mixed planting densities compared with that of solitary crops. Maize yield and water use efficiency were improved under the same-high mixed planting density because of the improvement of root properties and the optimization of biomass distribution, in semi-arid region of China.